IMPLEMENTASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN - Sugeng Chairuddin; Fadhlurrahman Fadhlurrahman; Kristiana Habeahan (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
This study aims to determine Organizational Citizenship Behavior (OCB) in employees at the company. Organizational Citizenship Behavior (OCB) as individual behavior that is discretionary, not directly or explicitly recognized by a formal reward system, and in the aggregate promotes the effective functioning of the organization Excellent performance of demanding employee behavior is expected by the organization. The behavior demanded by organizations today is not only in-role behavior but also extra-role behavior. Extra-role behavior is also known as Organizational Citizenship Behavior (OCB) is a term used to identify employee behavior that can be called good employees. If employees in the organization have OCB, the effort to control cadets decreases, because employees can control their own behavior or are able to choose the best behavior for the benefit of the organization. The results of the analysis in this study show that the Organizational Citizenship Behavior (OCB) of employees has shown good behavior that can support the success of the organization.